Coarse snapshots of oxygen-dissociation intermediates of a giant hemoglobin elucidated by determining the oxygen saturation in individual subunits in the crystalline state. (2021) - Numoto, Nobutaka; Kawano, Yoshiaki; Okumura, Hideo; Baba, Seiki; Fukumori, Yoshihiro; Miki, Kunio; Ito, Nobutoshi
No abstract available